Contextual analysis of work accidents in the nursing team - Yanna Gomes de Sousa; Ana elisa Pereira chaves; Laura Raquel Araújo de Morais; Soraya Maria de Medeiros; Marília Souto de Araujo; Karla Morgana da Costa Félix Assis (Universidad de Alicante, 2019)
Objective: The objective was to analyze the contextual aspects that influence the work accidents in the nursing team. Method: Narrative review at the SciELO, LILACS and MEDLINE databases. The material was analyzed in light of the Context Analysis model, which indicates four layers of interactive contextual relations of the phenomena that facilitate its comprehension (immediate, specific, general and metacontextual). Results: The data were presented in subtopics: work accidents with nursing professionals, work activities of the nursing professional in a hospital unit, psychosocial repercussions of accidents at work and legislation on work accidents in Brazil. Conclusions: The meaning of the studied phenomenon was better understood, making it possible to be shared and used in nursing practices.